An affordable solution for micro-miners in Colombia to process gold ores without mercury. (20th December 2018) - Veiga, Marcello M.; Masson, Pierre; Perron, Denis; Laflamme, Annie-Claude; Gagnon, Robert; Jimenez, Gabriel; Marshall, Bruce G.
Abstract: Simple and affordable pieces of equipment to concentrate gold were developed by the Colleges and Institutes Canada (CICAN) Project in Colombia using locally available materials found in junk yards and metal shops. A chain mill, shaking table and flotation cell were built in Colombia and demonstrated to micro-miners, who typically process less than 2 tonnes per day (tpd) of ore. An economic feasibility study was conducted for four different ore processing rates (0.2, 0.5, 1 and 2 tpd) and different levels of gold recovery (30, 50, 70 and 85%) that were compared with the current practice of taking ores to processing centers ( entables ), where the whole ore is typically amalgamated in small ball mills called cocos . For the processing rates of 0.2, 0.5 and 1 tpd, miners must sell their concentrates to cyanidation plants at 65% of the gold content. At 2 tpd, miners could further leach the concentrates with cyanide using a mill-leaching technique. Although the results show that the CICAN approach is profitable at all levels of production, gold recovery must be higher than what is normally achieved at the entables using amalgamation (∼30%). For miners processing 0.5 tpd or less of ore, their recoveries must be much higher than 50% to be more profitable than using mercury in entables . Miners using the CICAN techniques of gravity and flotation concentration to process 1 tpd of ore with a gold grade of 15 g/t and 85% recovery would generate a Net Present Value of US$315, 693 with an Internal Rate of Return of 1754%. This would generate US$150, 000 more profit over a 5-year period when compared with miners taking their ores to entables . Even for the micro-miners who have no capacity to leach gold from the concentrates using cyanide, the CICAN techniques are very feasible, as they can sell the concentrates afterwards for a value above 65% of the gold content. The capital cost for the CICAN equipment ranges from US$ 2, 600 (0.2 tpd) to US$ 10, 500 (2 tpd) and the estimated operating cost fluctuates between US$ 4, 500 (0.2 tpd) and US$ 10, 309 (2 tpd). Highlights: Micro-miners processing <2 tpd can build affordable concentration equipment. Chain mills, shaking tables and flotation cells were built using local materials. Economic feasibility assessment for 0.2, 0.5, 1 and 2 tonnes of ore per day. Gold recovery must be higher than 50% to generate better profits than entables. Selling concentrates for a price of 65% of the gold content is profitable.